Effect of Sand Sphericity and Cement-to-sand Ratio on Effective Porosity and Permeability of Concrete Sand Filter - Pradana, Gregorius Signer; Kamulyan, Budi; Supraba, Intan (Universitas Negeri Yogyakarta, 2024)
Sand filter is a widely used water treatment technology due to its operational simplicity. The drawbacks of sand filter operation are long backwash times and particle stratification, leading to high energy and sand replacement costs. The concrete sand filter (CSF) was created by mixing sand with cement paste as a binding agent. CSF establishes its water production capacity based on its effective porosity and permeability, which are influenced by the shape of the sand. CSF may have more spherical particles because the cement paste covers the sand. Previous studies have investigated the influence of the shape and size of aggregates on the porosity and permeability of pervious concrete. This study investigates the effective porosity and permeability of CSF using various sand shapes and cement-to-sand (c:s) ratios, as well as changes in the shape of the sand grains used to build the CSF due to mixing with cement paste. The sand types are characterized by their circle ratio sphericity; the c:s ratios tested are 0, 1:6.4, and 1:8.6. All specimens are 10.9 cm in diameter and 20 cm in height. The water displacement method was employed to measure the effective porosity, while the constant head method was used to determine the permeability. The results indicate that when the circle ratio sphericity of the sand used to build the filter increases, the effective porosity and permeability of filters decrease for all values of c:s. Specimens with high cement content have lower effective porosity and permeability and show a strong linear relationship (R² = 0.9555 at c:s = 1:6.4).